Community pharmacy lifestyle intervention to increase physical activity and improve cardiovascular health of men with prostate cancer: a phase II feasibility study. Issue 6 (11th June 2019) - Lemanska, Agnieszka; Poole, Karen; Griffin, Bruce A; Manders, Ralph; Saxton, John M; Turner, Lauren; Wainwright, Joe; Faithfull, Sara
Abstract : Objectives: To assess the feasibility and acceptability of a community pharmacy lifestyle intervention to improve physical activity and cardiovascular health of men with prostate cancer. To refine the intervention. Design: Phase II feasibility study of a complex intervention. Setting: Nine community pharmacies in the UK. Intervention: Community pharmacy teams were trained to deliver a health assessment including fitness, strength and anthropometric measures. A computer algorithm generated a personalised lifestyle prescription for a home-based programme accompanied by supporting resources. The health assessment was repeated 12 weeks later and support phone calls were provided at weeks 1 and 6. Participants: 116 men who completed treatment for prostate cancer. Outcome measures: The feasibility and acceptability of the intervention and the delivery model were assessed by evaluating study processes (rate of participant recruitment, consent, retention and adverse events), by analysing delivery data and semi-structured interviews with participants and by focus groups with pharmacy teams. Physical activity (measured with accelerometry at baseline, 3 and 6 months) and patient reported outcomes (activation, dietary intake and quality of life) were evaluated. Change in physical activity was used to inform the sample size calculations for a future trial. Results: Out of 403 invited men, 172 (43%) responded and 116 (29%) participated. Of these, 99 (85%) completed the intervention and 88 (76%) completed the 6-month follow-up (attrition 24%). Certain components of the intervention were feasible and acceptable (eg, community pharmacy delivery), while others were more challenging (eg, fitness assessment) and will be refined for future studies. By 3 months, moderate to vigorous physical activity increased on average by 34 min (95% CI 6 to 62, p=0.018), but this was not sustained over 6 months. Conclusions: The community pharmacy intervention was feasible and acceptable. Results are encouraging and warrant a definitive trial to assess the effectiveness of the refined intervention.